The Perception of Multiculturalism in Malaysian Visual Art University Students’ Paintings - Hajianfard, Ramin; Mokhtar, Elis Syuhaila Binti; Rafee, Yakup Bin Mohd (Universitas Negeri Semarang, 2024)
Malaysia’s diverse population has influenced people’s lives in many areas, from fashion and cuisine to art and interpersonal relationships. The country’s diverse atmosphere has shaped the perspectives of young artists from different ethnic backgrounds, affecting their artistic expression and their ability to incorporate multicultural themes in their works. This study aims to find out how multiculturalism is perceived by young Malaysian artists from the country’s major ethnic groups - Malays, Chinese and Indians - and the feelings they express in their artworks. This study adds to the body of knowledge on multiculturalism from the perspective of young Malaysian artists by examining their visual perceptions. The study examines the works of these artists through a formal and contextual analysis. While the contextual analysis explores themes such as people, architecture and cuisine, the formal analysis focuses on visual components such as line, colour, texture and composition. The integration of these approaches helps to identify the preferences of the participants (the artists who created these paintings) and the cultural elements that appear in their works. The results of this study have shown that young Malaysian artists have frequently used symbolic colours to represent the different ethnic groups in Malaysia, along with repetitive motifs that show the connection and unity between different cultural elements. These findings show a new generation’s perspective on multiculturalism and provide an insight into the way young Malaysian artists perceive and communicate the complexity of diversity and how it manifests itself in the visual arts. These artworks show the harmony between diversity and unity and the influence of Malaysia’s multicultural society on the artistic output of the country’s youth.